Innovation and sustainability in the disruptive era: The case of a new Malaysia - Shuaib, Farid Sufian (2019)
The paper examines the innovation and sustainability of the innovation in the period after the 14th General Election. The disruption to the then government of the day provides possibilities of innovation to the constitutional politic of Malaysia. The paper looks at the innovation offered by the new government. The paper finds issues with sustainability of those innovations.